2006
DOI: 10.1002/ana.20857
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic source imaging versus intracranial electroencephalogram in epilepsy surgery: A prospective study

Abstract: MSI yields localizing information with a high positive predictive value in epilepsy surgery candidates who typically require ICEEG. This finding suggests that enough clinical validity exists for MSI to potentially replace ICEEG for seizure localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
118
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 31 publications
2
118
0
Order By: Relevance
“…Thus, our presurgical approach may potentially replace invasive monitoring for seizure localization in many patients with TSC. 12 This study also shows that younger age at surgery and shorter seizure duration was associated with higher rate of seizure freedom after surgery. Conversely, longer seizure duration was associated with lower rate of seizure freedom after surgery.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Thus, our presurgical approach may potentially replace invasive monitoring for seizure localization in many patients with TSC. 12 This study also shows that younger age at surgery and shorter seizure duration was associated with higher rate of seizure freedom after surgery. Conversely, longer seizure duration was associated with lower rate of seizure freedom after surgery.…”
supporting
confidence: 57%
“…For this study, dipole clusters were defined as 5 or more epileptiform dipoles in 1 or contiguous sublobar regions of the brain. 12 By chance, patients 5 and 16 had seizures during their magnetoencephalography (MEG) studies (table 1), and the ictal onset zone closely matched the region localized by the interictal dipoles in the same study. Whereas 1 patient who had MSI elected not to undergo surgery, the other 13 children underwent surgery, with the final resection based on all noninvasive tests, and the intraoperative electrocorticography.…”
mentioning
confidence: 77%
“…A loose cluster was defined by five or more dipoles located within one sublobar region. Sublobar regions were defined using a common classification scheme (frontopolar, superior frontal, inferior frontal, mesial frontal, superior parietal, inferior parietal, mesial parietal, lateral occipital, mesial occipital, temporopolar, lateral temporal, and mesial temporal) (Knowlton et al, 2006;Schneider et al, 2012). A scattered cluster was defined by five or more dipoles involving more than one sublobar region.…”
Section: Definition Of Cluster Tightness and Orientationmentioning
confidence: 99%
“…Key advantages of MEG include non-invasiveness, high temporal and spatial resolution, and an ability to provide a broad whole-head view of brain activities. In many studies, MEG has been demonstrated to add non-redundant information to guide implantation sites for intracranial recordings (Knowlton et al, 2006;AgirreArrizubieta et al, 2014), resulting in changes to surgical treatment and medical management (Sutherling et al, 2008;Ito et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that this method can provide reliable and useful information in presurgical patients with partial epilepsy (Stefan et al, 2003;Wu et al, 2006;RamachandranNair et al, 2007), and have concluded that non-invasive MEG techniques might eventually partly replace invasive intracranial recording techniques (Pataraia et al, 2004;Papanicolaou et al, 2005;Knowlton et al, 2006). However, the analysis procedures require that each dipole is manually reviewed and classified as either corresponding to a real spike or as corresponding to a non-epileptic origin, which can be timeconsuming, requires trained and experienced scorers, and introduces a sizeable amount of subjectivity in the results.…”
Section: Introductionmentioning
confidence: 99%